2017
DOI: 10.5539/jas.v9n11p283
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Basil Genotypes to Salinity

Abstract: Basil (Ocimum basilicum L.) is a medicinal species of Lamiaceae family, popularly known for its multiple benefits and high levels of volatile compounds. The species is considered to be one of the most essential oil producing plants. Also cultivated in Brazil as a condiment plant in home gardens. The objective of this study was to evaluate the effect of salinity on the growth of basil in nutrient solution of Furlani and to identify variables related to the salinity tolerance in this species. The first assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Identically to the observation of Maggio et al [ 41 ], an interaction between the genetic background of the different cultivars and the different concentrations of the nutrient solution was obvious, specifically in the case of fresh and dry biomass. Each cultivar achieved the best production with a specific nutrient solution, highlighting how tolerance to the concentration of salts in the nutrient solution is highly dependent on the genotype [ 38 , 42 ]. The use of nutrient solution 2 dS m −1 determined on average an increase of Aroma 2 fresh biomass of about 30% compared to those recorded with the other two nutrient solutions, confirming how the yield is negatively affected by nutrient solutions that are too concentrated and/or too diluted [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identically to the observation of Maggio et al [ 41 ], an interaction between the genetic background of the different cultivars and the different concentrations of the nutrient solution was obvious, specifically in the case of fresh and dry biomass. Each cultivar achieved the best production with a specific nutrient solution, highlighting how tolerance to the concentration of salts in the nutrient solution is highly dependent on the genotype [ 38 , 42 ]. The use of nutrient solution 2 dS m −1 determined on average an increase of Aroma 2 fresh biomass of about 30% compared to those recorded with the other two nutrient solutions, confirming how the yield is negatively affected by nutrient solutions that are too concentrated and/or too diluted [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basil ( Ocimum basilicum L.) is an important warm-season MAP with high potential to be integrated into a wealth of cropping systems [ 14 , 15 ]. The salinity tolerance of basil is considered low [ 16 ], and the variability of the responses depends on numerous factors that include the genotype, the growing medium and conditions, including the presence in the soil of microbes with either pathogenic or beneficial activity [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Such responses are multidimensional because they affect main parameters of economic importance, such as the leaf fraction on the total above-ground biomass, and the concentration and composition of secondary compounds, including the volatile organic fractions and the essential oil [ 14 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The seedlings were prepared from seeds obtained from Isla Sementes Ltda®. The genotypes 'Toscano folha de alface' (TFA) and 'Gennaro de menta' (GM), were classified as salt-tolerant and salt-sensitive in a preliminary experiment (Menezes et al, 2017) in which, it was found that 80 mM NaCl did not affect the biomass production of the leaves of the TFA, but decreased it by 61% in case of GM. The experimental design was a randomized block in factorial arrangement with 2 (genotypes) × 2 (salt levels), and six replications, each consisting of 12 plants.…”
Section: Location Experimental Procedures and Treatmentsmentioning
confidence: 99%
“…The seeds were sown in 150 mL plastic cups containing washed coconut fiber, irrigated daily with water from the local supply company. At 19 days after emergence (DAE), with the second pair of leaves fully expanded, the seedlings were transferred to the DFT hydroponic cultivation system (Menezes et al, 2017), with plant spacing of 0.20 m. The nutrient solution (NS) of Furlani (1998), specific for leafy vegetables (Table 1), was used for the cultivation. After 2 days of acclimation, the seedlings received respective salt treatments (0 -control or 80 mM NaCl).…”
Section: Location Experimental Procedures and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation